Recent advances in C–S bond formation via C–H bond functionalization and decarboxylation. (13th October 2014) - Shen, Chao; Zhang, Pengfei; Sun, Qiang; Bai, Shiqiang; Hor, T. S. Andy; Liu, Xiaogang
Abstract : The development of mild and general methods for C–S bond formation has received significant attention because the C–S bond is indispensable in many important biological and pharmaceutical compounds. Abstract : The development of mild and general methods for C–S bond formation has received significant attention because the C–S bond is indispensable in many important biological and pharmaceutical compounds. Early examples for the synthesis of C–S bonds are generally limited to the condensation reaction between a metal thiolate and an organic halide. Recent chemical approaches for C–S bond formation, based upon direct C–H bond functionalization and decarboxylative reactions, not only provide new insights into the mechanistic understanding of C–S coupling reactions but also allow the synthesis of sulfur-containing compounds from more effective synthetic routes with high atom economy. This review intends to explore recent advances in C–S bond formation via C–H functionalization and decarboxylation, and the growing opportunities they present to the construction of complex chemical scaffolds for applications encompassing natural product synthesis, synthetic methodology development, and functional materials as well as nanotechnology.